Hydrogen sulfide (H2 O) Removal Technologies from Biogas Production (International Journal of Food and Nutritional Sciences, 2022)
Because of growing energy demand and environmental concerns, the prospect of producing heat or power from renewable sources, like biogas, is expanding in the present energy situation. A fermentation and biohydrogen thermal reformation may be used to make biohydrogen digester fuel, and the energy can be generated using proton exchange membrane fuel cells. Pollutants (sulfur compounds, halogenated hydrocarbons, and siloxanes, for example, hydrogen sulfide (H2S) at 100 to 10000 ppm) are often encountered in manufacturing. The concentration of pollutants is determined by the kind of biomass or organic waste. Sulfur compounds are removed using a variety of purification procedures, although not all of them can decrease sulfur to ultralow stages. Additionally, few investigations on biogas upgrading from sulfur particles for fuel cell application have been published. We evaluate and discuss gas-separation methods for removing H2S from biogas production in this research. The effectiveness and efficiency of the separation system are examined in terms of the H2S elimination unit's mechanisms and operating process, includes the design, technique, and materials used in uptake. After all, the strategies for removing H2S through adsorption have recently been improved by modifying cellulose Nano/microcrystals technologies for increased adsorption effectiveness.